Investigation of skin‐core joints in aluminium foam sandwich panels by EDS and XPS. (16th December 2015) - Lapi, G.; Montanari, R.; Tata, M. E.; Barbieri, G.; Balijepalli, S. K.; Kaciulis, S.
Abstract : Al foams are used to produce aluminium foam sandwiches (AFS) panels or other mechanical parts of complex shape, which are of great interest for many industrial applications. AFS panels with a core made of AlSi10 foam and the skins of AISI 316 steel have been prepared by in situ bonding process. To optimise the process conditions, a first set of experiments has been carried out to realise samples of reduced lab scale (20 × 20 mm 2 ), then the AFS panels of pre‐industrial size (100 × 100 mm 2 ) have been produced. The steel‐foam joints were investigated by scanning electron microscopy, energy dispersion spectroscopy and X‐ray photoelectron spectroscopy. The performed examinations showed that the interface formed during the foaming was characterised by a good inter‐diffusion of alloying elements, testifying the excellent quality of metallurgical joints. Furthermore, the pre‐industrial panels exhibited the same characteristics of lab samples; therefore, it can be concluded that the scale‐up process has been implemented successfully. Copyright © 2015 John Wiley & Sons, Ltd.